Cardiovascular Biomarkers in Amniotic Fluid, Umbilical Arterial Blood, Umbilical Venous Blood, and Maternal Blood at Delivery, and Their Reference Values for Full-Term, Singleton, Cesarean Deliveries - Blohm, Martin E.; Arndt, Florian; Fröschle, Glenn M.; Langenbach, Nora; Sandig, Jan; Vettorazzi, Eik; Mir, Thomas S.; Hecher, Kurt; Weil, Jochen; Kozlik-Feldmann, Rainer; Blankenberg, Stefan; Zeller, Tanja; et al. (Frontiers in Pediatrics, 2019)
Background: Several cardiovascular biomarkers have regulatory functions in perinatal physiology. Aim: This study aimed to analyze the feto-maternal distribution pattern of biomarkers in samples of amniotic fluid, umbilical arterial blood, umbilical venous blood, and maternal blood samples, and to establish reference values. Each linked sample set consisted of the combined samples obtained in an individual pregnancy. Study design: We performed a prospective, observational, cross-sectional, single-center study. Subjects: The sample cohort included 189 neonates who were born to 170 mothers. A total of 162/189 neonates were full term and 129/189 were delivered by elective cesarean section. Outcome measures: Midregional pro-adrenomedullin (MRproADM [nmol/L]), midregional pro-atrial natriuretic peptide (MRproANP [pmol/L]), brain natriuretic peptide (BNP [pg/mL]), N-terminal pro-brain natriuretic peptide (NTproBNP [pg/mL]), copeptin [pmol/L], and high-sensitive troponin I (hsTnI [pg/mL]) levels were measured. Results: In singleton, full-term, primary cesarean deliveries (n=91), biomarker levels (median, [IQR]) at delivery were as follows. MRproADM levels in umbilical arterial blood/umbilical venous blood/amniotic fluid/maternal blood were 0.88 (0.20)/0.95 (0.18)/2.80 (1.18)/1.10 (0.54), respectively. MRproANP levels were 214.23 (91.38)/216.03 (86.15)/0.00 (3.82)/50.67 (26.81), respectively. BNP levels were 14.60 (25.18)/22.08 (18.91)/7.15 (6.01)/6.20 (18.23), respectively. NTproBNP levels were 765.48 (555.24)/816.45 (675.71)/72.03 (55.58)/44.40 (43.94), respectively. Copeptin levels were 46.17 (290.42)/5.54 (9.08)/9.97 (7.44)/4.61 (4.59), respectively. Levels of hsTnI were 6.20 (4.25)/5.60 (5.01)/0.45 (1.73)/2.50 (2.40), respectively. Conclusion: We determined reference values for biomarkers in term neonates delivered by primary cesarean section in amniotic fluid, umbilical arterial and venous blood, and maternal blood. Biomarkers in the fetal circulation appear to be of primary fetal origin, except for MRproADM.